1988
DOI: 10.1111/j.1365-246x.1988.tb03431.x
|View full text |Cite
|
Sign up to set email alerts
|

Teleseismic travel-time anomalies and deep crustral structure in central Australia

Abstract: Teleseismic travel times have been recorded along two lines of instruments traversing the Amadeus Basin and southern Arunta Block of central Australia for the purpose of examining the deep crustal and upper-mantle structure underlying these features. Pronounced differential travel times, approaching 1.5 s, and with major azimuthal variation, have been recorded. Most of the useful observations originated from events to the north (JapanMarianas) and to the east (Fiji-Tonga) at epicentral distances of 40-65". A f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The initial application of mapping of the relative delay times of seismic arrivals was to investigate the major gravity anomalies in central Australia ( Figure 5) by using linear profiles of portable instruments (Lambeck et al, 1988). These studies revealed the need for substantial, but localised, variations in crustal thickness, to satisfactorily model the seismic results.…”
Section: Body-wave Tomographymentioning
confidence: 99%
“…The initial application of mapping of the relative delay times of seismic arrivals was to investigate the major gravity anomalies in central Australia ( Figure 5) by using linear profiles of portable instruments (Lambeck et al, 1988). These studies revealed the need for substantial, but localised, variations in crustal thickness, to satisfactorily model the seismic results.…”
Section: Body-wave Tomographymentioning
confidence: 99%
“…[19] Current knowledge of the crustal architecture of the Musgrave Province at depth is based on a single teleseismic transect across the province [Lambeck and Burgess, 1992;Lambeck et al, 1988], supplemented by deep seismic reflection data in the Amadeus Basin [Korsch et al, 1998] and at the southern margin of the Musgrave Province [Lindsay and Leven, 1996] (Figure 2). The model based on teleseismic data (Figure 3) is characterized by steep Moho penetrating shear zones, corresponding to the Mann Fault, Wintiginna Lineament and Lindsay Lineament, that accommodate an upward Moho offset of up to 30 km beneath the central Musgrave Province [Lambeck and Burgess, 1992].…”
Section: Crustal Architecture Of the Musgrave Provincementioning
confidence: 99%
“…[4] Seismic and gravity data over the Arunta Inlier have provided a reasonable degree of constraint on the crustal architecture of this province and have demonstrated that the crust-mantle boundary is uplifted by $25 km along the lithospheric scale Redbank Thrust Zone, and that this offset is sufficient to cause the relative gravity high [Goleby et al, 1989[Goleby et al, , 1990Korsch et al, 1998]. A similar but less well constrained model derived from teleseismic data over the Musgrave Province proposes up to 30 km of crust-mantle boundary uplift, occurring along steep lithospheric scale reverse shear zones during the Petermann Orogeny [Lambeck and Burgess, 1992;Lambeck et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Moho depth varies between 37 and 53 km along the BILBY transect. The crust beneath the Musgrave Province, Officer Basin, and Arunta Block is characterized by a Moho uplift, which might be due to the presence of crustal‐scale faults and shear zones (e.g., Redbank shear zone in Arunta block [Goleby et al., 1989; Lambeck & Penney, 1984; Lambeck et al., 1988; Sippl, 2016]). A distinct and systematic pattern of Moho variation is recognizable along the transect across the crustal domains.…”
Section: ‐D Results and Discussionmentioning
confidence: 99%